The angles within the triangle are α, β and γ (where α is opposite a, and so on).
Now, drop a perpendicular from α onto side a, such that it splits a into lengths x and y (with x on the side closer to angle γ).
Then, we can see that:
cosβ = y / c | and | cosγ = x / b | |
∴ | y = c cosβ | and | x = b cosγ |
∴ | a = b cosγ + c cosβ | ||
∴ | a2 = ab cosγ + ac cosβ [1] |
Now, in our triangle, we could also drop a perpendicular from β to b and from γ to c, and by going through the same process as above, we would end up with similar equations, but with:
a→b→c→a and α→β→γ→α in one, and
a→c→b→a and α→γ→β→α in the other.
Resulting in:
b2 = bc cosα + ab cosγ [2] and
c2 = ac cosβ + bc cosα [3]
Now, if we take the three equations, and do [3] - [2] - [1], we have:
c2 - b2 - a2 =
∴ c2 = a2 + b2 - 2ab cosγ
And this is the cosine rule. I have to confess that this is a small, but clearly important, piece of maths that I had either completely forgotten, or never come across in the first place.
The reason for mentioning it here is that at the weekend I spent a while working on a question from Jake's maths homework for him, and finally managed to come up with the answer.
Jake was pleased with my help, but came back to me a few minutes later and pointed out that it could have been done in a fraction of the time that I had taken, by the simple application of the cosine rule!
Oh dear. I sense that I am going to start struggling to keep up very soon ....